Phenotypes of Allergic Asthma: Does In-Vitro Allergy Testing Help Predict Asthma Disease Severity?. Issue 6 (November 2022) - Benninger, Michael S.; Cabrera, Claudia I.; Amador, Eulalia M.; Grafmiller, Kevin; Sindwani, Raj
Background: Allergy and asthma are often diagnosed concomitantly. Patients with both diagnoses might need to have a more targeted approach to reduce the symptomatic burden and severity of disease. Objective: This study was designed to explore the relationship between specific allergen sensitization, and asthma diagnosis and severity with the hypothesis that patients who tested positive to a higher allergy class of response and to more allergens would be more likely to have severe asthma. Methods: A retrospective review was performed on 1419 charts that had a positive IgE allergy class blood test between 2014 and 2018. A total of 701 patients had one or more positive tests and a diagnosis of asthma. Patient demographics and pertinent variables including all clinic and ED visits, specific allergy and class of response, and information related to their asthma treatment and severity were recorded. Logistic regression was used to analyze the likelihood of asthma diagnosis, concomitant diagnosis of asthma and allergic rhinitis, and measures of asthma severity. Results: Higher class of response to cat dander 1.24 (1.09, 1.41), dog dander 1.29 (1.13, 1.47), lamb's quarter 1.35 (1.06, 1.70), house dust 1.41 (1.11, 1.82), Cladosporium herbarum 1.35 (1.07, 1.67) or cockroach 1.56 (1.00, 2.44) showed increased odds of hospitalizations. There was a statistically significant difference between the average number of classes for patients with and without asthma ( P < .001), and those with and without steroids ( P < .001). Conclusions: This study found that positivity to cat dander, dog dander, some fungus, and house dust was associated with more severe asthma.